Factores de interés referentes a la colonización de haemagogus splendens para experimentos de transmisión con virus de fiebre amarilla en el laboratorio (1947)
1o The known geographic distribution of Haemagogus splendens is extended, and its role as a probable vector in natural conditions is established. 2 o H. splendens of all the species of Haemaqogus, is the one that seems to constitute a biological link between that genus and the genus Aedes. (Based on the great similarity of behavior with Aedes aegypti under laboratory conditions). 3 o The identification of females is most easy. 4 o A technique for egg laying and transportation of the adults is described.